Contemporary Advances in Innovative and Applicable Information Technology Proceedings of ICCAIAIT 2018 - Mandal, Jyotsna Kumar; Sinha, Devadatta; Bandopadhyay, J.P (Advances in Intelligent Systems and Computing, 2019)
XXII, 246 p. 103 illus.